Payment Cards and Permitted Multilateral Interchange Fees (MIFs): Will the European Commission Harm Consumers and the European Payment Industry?. (21st November 2014) - De Matteis, Andrea; Giordano, Simone
Abstract: Since 1992, the European Commission has checked the legality with the competition rules of the multilateral interchange fees (MIFs) that are set by payment card schemes. The latest judgment issued by the Court of Justice has brought no light to the fundamental issue of what levels of MIFs would be permissible. The European Commission is now addressing the matter with a regulation which, if approved in its current form, would allegedly harm consumer welfare and the European payment industry.